The Application Prospects of Virtual Reality (VR) and Augmented Reality (AR) Technologies in the Sports Industry - Taking Winter Ice and Snow Events as an Example - Li, Wangcheng (Transactions on Economics, Business and Management Research, 2024)
With the continuous advancement of technology and the expansion of application scenarios, both AR and VR have broad development prospects. Based on the increasingly mature technology, can VR and AR technology be brought into sports, what role can they play in various sports projects, and what prospects do they have in the sports industry. In winter sports, heavy competitive events, and many training events, athletes can simulate training anytime and anywhere to understand their opponents. In theory, promoting VR and AR into the sports industry can bring heavy competitive sports and winter events to the masses, allowing more people to experience the charm of sports more accurately and intuitively. The application of VR and AR technology in the sports industry, especially in winter ice and snow events, not only demonstrates its strong potential, but also heralds new directions for the future development of the sports industry. Through these technologies, athletes have gained more efficient training methods, while audiences can also enjoy a more immersive and interactive viewing experience. Despite some technological and market challenges, with the continuous advancement of technology and the expansion of application fields, the role of VR and AR technology in the sports industry will become increasingly significant.